2018
DOI: 10.1002/ppul.23934
|View full text |Cite
|
Sign up to set email alerts
|

A bench study of inhaled nitric oxide delivery during high frequency percussive ventilation

Abstract: The dual gas delivery system of the Bronchotron prevents accurate delivery of INO. The combination of these two devices should be accomplished with caution and vigilance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…28 In a study by Branson et al, multiple configurations of a Bronchotron Transport Ventilator and iNO delivery system (INOmax DSIR Plus) showed that the dual gas delivery system of the Bronchotron prevents accurate delivery of iNO, failing to deliver iNO within 30% of the set concentrations. 28 Due to the limited availability of Bronchotrons and their incompatibility with iNO, a therapy commonly utilized in this patient population, many institutions are unable to transfer neonates with CDH who are on HFOV with or without iNO to hospitals that can accommodate advanced treatment such as cannulation onto ECMO. Finally, utility outside of the intensive care unit (ICU) such as in the operating room is limited as the vibrations of the oscillator impair the surgeon's ability to repair the defect and anesthesiologists may be less familiar with this mode of ventilation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 In a study by Branson et al, multiple configurations of a Bronchotron Transport Ventilator and iNO delivery system (INOmax DSIR Plus) showed that the dual gas delivery system of the Bronchotron prevents accurate delivery of iNO, failing to deliver iNO within 30% of the set concentrations. 28 Due to the limited availability of Bronchotrons and their incompatibility with iNO, a therapy commonly utilized in this patient population, many institutions are unable to transfer neonates with CDH who are on HFOV with or without iNO to hospitals that can accommodate advanced treatment such as cannulation onto ECMO. Finally, utility outside of the intensive care unit (ICU) such as in the operating room is limited as the vibrations of the oscillator impair the surgeon's ability to repair the defect and anesthesiologists may be less familiar with this mode of ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…Bronchotron Transport Ventilators can provide similar ventilatory support; however, they are not widely available and have shown to be incompatible with iNO. 28 In a study by Branson et al, multiple configurations of a Bronchotron Transport Ventilator and iNO delivery system (INOmax DSIR Plus) showed that the dual gas delivery system of the Bronchotron prevents accurate delivery of iNO, failing to deliver iNO within 30% of the set concentrations. 28 Due to the limited availability of Bronchotrons and their incompatibility with iNO, a therapy commonly utilized in this patient population, many institutions are unable to transfer neonates with CDH who are on HFOV with or without iNO to hospitals that can accommodate advanced treatment such as cannulation onto ECMO.…”
Section: Discussionmentioning
confidence: 99%
“…Elastance and resistance can also be estimated through an external monitor during HFPV with acceptable accuracy (61). It is not possible to precisely deliver inhaled nitric oxide during HFPV (62).…”
Section: Bench Studiesmentioning
confidence: 99%
“…The aim of this study is to implement a method capable of administering CO 2 to both ventilated and non-ventilated patients. In contrast to other CO 2 administration methods, our method does not generate the entire gas mixture but, instead, supplements the inspired gas with additional CO 2 in proportion to the respiratory gas flow, as illustrated in Figure 1 , drawing inspiration from nitric oxide systems ( 15 ). This approach does therefore not rely on the addition of external reservoirs or multiple gas sources, keeping the necessary modification of the breathing circuit minimal, which is desirable in an intensive care setting.…”
Section: Introductionmentioning
confidence: 99%